2020
DOI: 10.3389/fmicb.2020.563047
|View full text |Cite
|
Sign up to set email alerts
|

Bryophytes Harbor Cultivable Actinobacteria With Plant Growth Promoting Potential

Abstract: This study was designed to investigate the cultivable actinobacteria associated with bryophytes and their plant growth promoting ability. Thirteen actinobacteria were isolated and tested for their ability to promote growth of plant in vitro and in planta . All isolates were able to produce IAA and siderophores. Six isolates were identified as members of the genus Micromonospora . Five isolates belonged to the genus Streptomyces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 89 publications
0
11
0
Order By: Relevance
“…The phyla, Proteobacteria, Actinobacteria, Bacteroidetes, and Firmicutes have been reported to be widely distributed on the fruit surface of plant species, and contain a variety of taxa with different ecological roles, functioning as antagonists, symbionts (especially endophytes), and saprophytes ( Insuk et al, 2020 ; Lee et al, 2020 ; Mamphogoro et al, 2020 ). Actinobacteria have been reported to have a higher abundance in the endophytic community of kiwifruit cultivars that are more resistant to bacterial canker ( Cho et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The phyla, Proteobacteria, Actinobacteria, Bacteroidetes, and Firmicutes have been reported to be widely distributed on the fruit surface of plant species, and contain a variety of taxa with different ecological roles, functioning as antagonists, symbionts (especially endophytes), and saprophytes ( Insuk et al, 2020 ; Lee et al, 2020 ; Mamphogoro et al, 2020 ). Actinobacteria have been reported to have a higher abundance in the endophytic community of kiwifruit cultivars that are more resistant to bacterial canker ( Cho et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Actinobacteria have been reported to have a higher abundance in the endophytic community of kiwifruit cultivars that are more resistant to bacterial canker ( Cho et al, 2018 ). Insuk et al (2020) assessed the in vitro and in vivo growth- promoting activity of 13 strains of Actinomycetes isolated from bryophytes. They found that all of the tested isolates produced IAA and also sequestered iron, which promoted the growth of bryophytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigation of actinobacteria from lower plants, such as bryophytes (including mosses), and their beneficial traits are still rare. Recently, a member of the actinobacteria genus Micromonospora was reported from bryophytes, which showed plant growth-promoting activity in vitro and in planta [12]. Such a result suggests a potentially important role of actinobacteria in mosses.…”
Section: Introductionmentioning
confidence: 97%
“…They play important roles in food web dynamics, carbon and nutrient cycling, and soil temperature and moisture regulations [14]. Previous research has shown that moss-associated microbes are capable of enhancing the growth of the moss Physcomitrium sphaericum during its acclimatization from the laboratory environment to natural field soil [12], fix N 2 in the air [15], and contribute to the process of biomass decomposition [16].…”
Section: Introductionmentioning
confidence: 99%